1974
DOI: 10.1029/ja079i025p03773
|View full text |Cite
|
Sign up to set email alerts
|

Incoherent scatter measurements ofEregion conductivities and currents in the auroral zone

Abstract: Data taken by the incoherent scatter radar facility at Chatanika, Alaska, have been used to investigate ionospheric conductivities and electrical currents. During quiet days the conductivities appear to vary in a way consistent with ionization arising from solar EUV radiation. At these times the ratio between the height-integrated Hall and Pedersen conductivities is close to 2. In the evening hours, enhancements in the northward electric field are found to precede small increases in the conductivities that, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(112 citation statements)
references
References 20 publications
5
106
1
Order By: Relevance
“…Based on the contention of Kamide and Vickrey (1983) that the westward electrojet is conductivity dominated in the midnight and morning sector, and the observations by Brekke et al (1974) and Opgenoorth et al (1994) that the ratio H / P increases to >2:1 during active times in those sectors, we effectively increased H / P in the morning hours while keeping the evening sector conductivity ratio almost unchanged.…”
Section: Motivation For the Choice Of The Model Current Systemmentioning
confidence: 95%
“…Based on the contention of Kamide and Vickrey (1983) that the westward electrojet is conductivity dominated in the midnight and morning sector, and the observations by Brekke et al (1974) and Opgenoorth et al (1994) that the ratio H / P increases to >2:1 during active times in those sectors, we effectively increased H / P in the morning hours while keeping the evening sector conductivity ratio almost unchanged.…”
Section: Motivation For the Choice Of The Model Current Systemmentioning
confidence: 95%
“…(1). Magnetometer data was used to obtain the height-integrated current density j whilst Hall and Pedersen conductivity observations (Brekke et al, 1974) were used to calculate more precise values for the Cowling conductivity. A mean value for L/J of 2.37 was obtained for an electric ®eld of % 43 mV/m (Hunsucker, 1977); using the equations of Richmond and data from the same event, a value of L/J of 3.13 was obtained (Hunsucker, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of the magnitude of fluctuations in the declination for several magnetic observatories in Canada for the years 1976 and 1981, the increased deviations in the declination as one proceeded north, were explained to be solely the result of a decreasing horizontal magnetic field component (Newitt 1991). Brekke et al (1974) studied incoherent scatter measurements of the E-region conductivities and currents in the auroral zone in Alaska. When comparing the results from the measurements at Chatanika against the geomagnetic variations at the nearby College observatory, they concluded that there was close agreement regarding the variations in the horizontal magnetic field, but not for the variations of the declination.…”
Section: Spatial Geomagnetic Variationsmentioning
confidence: 99%